1994
DOI: 10.1136/gut.35.5.615
|View full text |Cite
|
Sign up to set email alerts
|

Gastrin and somatostatin in Helicobacter pylori infected antral mucosa.

Abstract: Helicobacter pyloni infection is associated with increased meal stimulated gastrin secretion, but the reason for this is unknown. Sequence specific radioimmunoassays were used to measure the concentration of ot-amidated gastrin, the total progastrin product, and somatostatin in biopsy specimens of human antral mucosa. The antral concentrations of ct-amidated gastrin and of total progastrin products were significantly higher in H pyloni infected patients than in those not infected by this organism. In contrast,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
26
0
3

Year Published

1998
1998
2019
2019

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(32 citation statements)
references
References 27 publications
3
26
0
3
Order By: Relevance
“…Our observation that treatment with Hp WE significantly attenuated gastric luminal release of somatostatin is in keeping with the previous observation that luminal somatostatin levels as well as mucosal expression of somatostatin mRNA were significantly decreased in Hp -infected human gastric mucosa [41]. It has been suggested that the facilitated gastrin release in Hp - infected patients may be the result of a reduced or blocked release of antral somatostatin, but the underlying mechanism has not been explained [42]. Hypergastrinemia, observed in Hp -infected mucosa, was attributed to either inflammatory cytokines [43]and/or alkalinization of the antral part of the stomach due to the local rise in antral pH by prolonged elevation of ammonia in the gastric juice caused by the urease activity of Hp [44, 45].…”
Section: Discussionsupporting
confidence: 78%
“…Our observation that treatment with Hp WE significantly attenuated gastric luminal release of somatostatin is in keeping with the previous observation that luminal somatostatin levels as well as mucosal expression of somatostatin mRNA were significantly decreased in Hp -infected human gastric mucosa [41]. It has been suggested that the facilitated gastrin release in Hp - infected patients may be the result of a reduced or blocked release of antral somatostatin, but the underlying mechanism has not been explained [42]. Hypergastrinemia, observed in Hp -infected mucosa, was attributed to either inflammatory cytokines [43]and/or alkalinization of the antral part of the stomach due to the local rise in antral pH by prolonged elevation of ammonia in the gastric juice caused by the urease activity of Hp [44, 45].…”
Section: Discussionsupporting
confidence: 78%
“…Interestingly, the microflora also regulates gastrointestinal endocrine cells and the synthesis and/or release of neuroendocrine peptides and the amine serotonin which, in turn, may affect cell proliferation in the gastrointestinal epithelium [6]. Likewise, H. pylori infection is associated with a reduced volume density of somatostatin-immunoreactive cells in the antral mucosa [37] and with low tissue concentrations of this peptide [38]. Somatostatin is a potent inhibitor of cell proliferation, which implies that a reduced inhibitory drive on the proliferative compartments secondary to reduced availability of the peptide may have contributed to the increase in cell proliferation observed in the gastric mucosa of patients infected with H. pylori [24].…”
Section: Discussionmentioning
confidence: 99%
“…A subsequent explanation for hypergastrinemia has been proposed with the demonstration of the impaired synthesis and release of somatostatin by H. pylori . Since somatostatin in the stomach acts to suppress gastrin release, its reduction results in the loss of the paracrine control of gastrin release and thus to hypergastrinemia [13,14]. …”
Section: Acid Secretion In Peptic Ulcer Diseasementioning
confidence: 99%